Effect of audit firm industry specialization on cost of debt financing: Evidence from Ghana - Ebenezer Nana Yeboah; Zhou Yang; Benedict Arthur; Gabriel Kyeremeh (Cogent Business & Management, 2023)
This study examines whether audit firm industry specialization affects the cost of debt finance of business. We hypothesize that audit firm industry specialization reduces client cost of debt since auditors with industry specialization are more likely to deter and detect questionable accounting practices and report material errors and irregularities. Thus, utilizing data from Ghanaian listed and unlisted firms, the study finds that audit firm industry specialization reduces the cost of debt. The finding is consistent with a robustness test in which an alternative measure of the audit firm's industry expertise was utilised. The study further submits that the influence of audit industry specialization on the cost of debt is more pronounced in the low-earning companies than high-earning companies, while no significant difference in impact exists between private companies and state-owned companies.
Keywords: 650; audit firm; audit firm industry specialization; audit quality; cost of debt financing